Secure care pathway and standards: co-production process and implementation plans - Paul Sullivan; Beth-Anne Logan (Scottish Journal of Residential Child Care)
The development of the Secure Care Pathway and Standards sets out, for the first time, national standards of what support children and young people in Scotland should expect when in, or on the edges of, secure care. Launched in October 2020, the Standards seek to ensure support is provided before, during and after a stay in secure care and that the rights of children and young people, often facing extreme vulnerabilities and risks in their lives, are respected. When implemented, the Standards will deliver a consistent, unified approach to caring for vulnerable children in all council areas, and to all children placed in secure care in Scotland. Crucially, the Standards were developed using co-production methods alongside children and young people. This article describes some of the elements of that process, as well as the impact that the new Standards will have on young people's lives in Scotland.